UPLC-MS/MS Method for Givinostat in Rat Plasma: Development, Validation, in vivo Pharmacokinetics Study and in vitro Metabolic Stability Research - Zhan R; Liu Y; Wu J; Shen Y; Xu X; Lin G; Chen X (Drug Design, Development and Therapy)
Ruanjuan Zhan,1,* Yanan Liu,1,2,* Jun Wu,1,2 Yuxin Shen,1,2 Xinhao Xu,1,2 Guanyang Lin,1,2 Xiaocheng Chen1 1The First Affiliated Hospital of Wenzhou Medical University, Zhejiang, People’s Republic of China; 2School of Pharmaceutical Sciences, Wenzhou Medical University, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guanyang Lin; Xiaocheng Chen, Email 13867702133@163.com; cxcwzcn@139.comBackground: Givinostat, a potent histone deacetylase (HDAC) inhibitor, is promising for the treatment of relapsed leukemia and myeloma.Purpose: This study aimed to develop and verify a quick assay for the measurement of givinostat concentration using ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) with eliglustat as the internal standard (IS), establishing a basic pharmacokinetic profile for its pre-clinical application and metabolic stability in vitro.Methods: Sample preparation was performed via protein precipitation using acetonitrile. The analyte (givinostat) and IS were gradient eluted on a Waters ACQUITY UPLC BEH C18 column (1.7 μm, 2.1 × 50 mm) with 0.1% formic acid (A) and acetonitrile (B) as the mobile-phase system. The multiple reaction monitoring (MRM) in positive ion mode was used to detect the mass transition pairs for givinostat and IS as follows: m/z 422.01→ 186.11 for givinostat, and m/z 405.40→ 84.10 for IS, respectively.Results: In the bioanalytical method, good linearity was observed between 2 and 4000 ng/mL (r2=0.998). The intra- and inter-day precisions (RSD%) were lower than 15%, with an accuracy (RE%) of 95.8%– 108.6%. The recovery exceeded 90%, and the matrix effect was within the range of 98.2%– 107.6%. Additionally, this method was successful in evaluating pharmacokinetics in rats after an oral dose of 10 mg/kg givinostat. Finally, in vitro results showed that givinostat had a slow intrinsic clearance (CLint) value of 14.92 μL/min/mg protein with a half-life (t1/2) value of 92.87 min.Conclusion: Givinostat was rapidly absorbed and cleared slowly in vivo, and it was confirmed by in vitro experiments. This study provides a potential reference for givinostat in clinical studies.Keywords: givinostat, UPLC-MS/MS, rat plasma, pharmacokinetic study, in vitro metabolic stability